Uzbekistan Country Forest Note : The State of Forests and Forest Landscapes in Uzbekistan - World Bank (Washington, DC: World Bank, 2022)
This Country Forest Note offers an in-depth picture of the forest sector of Uzbekistan, viewed through a forest landscape lens, and provides guidance to help define goals and identify opportunities for the continued development of the sector. Despite a large number of current challenges, forest landscape management presents opportunities for sustainable development: increasing the forest area will provide additional benefits in terms of climate change. A holistic approach to soil degradation is required that includes improved livestock husbandry, soil management, and agricultural practices, all of which have a role to play. Leskhozes have a central role in transforming the forest sector and augmenting their capacity and skills needs to be an important consideration. Equally important is to encourage community participation through mahallas and create favorable conditions for private sector involvement. Strong government commitment and institutional and stakeholder buy-in and ownership are required to support the transition to more adaptive management in forestry. This transition is critical to address climate change issues, increased threats to forests, soil and water conservation, economic management of wood and non-wood forest products (NWFPs) from forested landscapes, and improvement of livelihoods of rural households.